2015
DOI: 10.1159/000433473
|View full text |Cite
|
Sign up to set email alerts
|

Network Meta-Analysis of Onychomycosis Treatments

Abstract: Background: Many onychomycosis treatments have not been directly compared in head-to-head clinical trials. Objective: To determine the relative efficacy of onychomycosis treatments using network meta-analysis (NMA). Methods: We conducted a systematic review and NMA of mycological cure rates. Results: Nineteen trials were included in the network. Terbinafine 250 mg was significantly superior to all treatments except itraconazole 400 mg pulse therapy. The itraconazole 400 mg pulse regimen was significantly super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
1
13
0
1
Order By: Relevance
“…PRO analyses of topical treatments are limited, likely in part because numerous studies have demonstrated the clinical superiority of oral medications [36,37]. Additionally, until recently, ciclopirox was the only topical drug approved for onychomycosis treatment in the US [36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRO analyses of topical treatments are limited, likely in part because numerous studies have demonstrated the clinical superiority of oral medications [36,37]. Additionally, until recently, ciclopirox was the only topical drug approved for onychomycosis treatment in the US [36].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, until recently, ciclopirox was the only topical drug approved for onychomycosis treatment in the US [36]. With the approval of efinaconazole and tavaborole in 2014, more QOL studies are warranted given the high cost and nonsuperiority of these medications to oral antifungals [37]. …”
Section: Resultsmentioning
confidence: 99%
“…[ 20 ] There was no much difference between the efficacy of the pure medication in this study and that in literature. [ 21 22 ] The efficacy of the combination treatment was higher than that of the laser therapy only in the previous research. [ 1 10 12 ] In summary, combined laser and medicine treatment for onychomycosis is effective.…”
Section: Discussionmentioning
confidence: 90%
“…Onychomycosis in children is rare, usually it comes from indirect environment contamination of trauma or dystrophic nails. 5,6 In addition there are other factors influencing as climate, prolonged use of occlusive footwear, repeated trauma to the nails, and genetic predisposition. 2,3,[7][8][9] Onychomycosis can cause cosmetic problem, pain, discomfort, and affect the emotional or psychosocial aspects of the patient, thus requiring optimal and total therapy.…”
Section: Kata Kunci: Antijamur Kombinasi Terapi Onikomikosis Efekmentioning
confidence: 99%